DKAL*: Constructing Executable Specifications of Authorization Protocols - Jeannin, Jean-Baptiste; Caso, Guido de; Chen, Juan; Gurevich, Yuri; Naldurg, Prasad; Swamy, Nikhil (Lecture Notes in Computer Science 7781, 2013)
Many prior trust management frameworks provide authorization logics for specifying policies based on distributed trust. However, to implement a security protocol using these frameworks, one usually resorts to a general-purpose programming language. When reasoning about the security of the entire system, one must study not only policies in the authorization logic but also hard-to-analyze implementation code. This paper proposes DKAL*, a language for constructing executable specifications of authorization protocols. Protocol and policy designers can use DKAL*’s authorization logic for expressing distributed trust relationships, and its small rule-based programming language to describe the message sequence of a protocol. Importantly, many low-level details of the protocol (e.g., marshaling formats or management of state consistency) are left abstract in DKAL*, but sufficient details must be provided in order for the protocol to be executable. We formalize the semantics of DKAL*, giving it both an operational semantics and a type system. We prove various properties of DKAL*, including type soundness and a decidability property for its underlying logic. We also present an interpreter for DKAL*, mechanically verified for correctness and security. We evaluate our work experimentally on several examples. Using our semantics, DKAL* programs can be analyzed for various protocol-specific properties of interest. Using our interpreter, programmers obtain an executable version of their protocol which can readily be tested and then deployed.
International Symposium on Engineering Secure Software and Systems (ESSOS 13)